KISAH ULAMA/KIAI SEBAGAI STRATEGI PENYAMPAIAN PESAN WARGA NAHDLATUL ULAMA ETNIK MADURA - Akhmad Haryono (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2014)
This article describes the telling of the story of adorable ulama/kiai (moslem religious leader) as communication strategy. The study uses the qualitative method by applying ethnography of communication approach. It collected the data through participatory observation and non participatory observation, interview, and recording. It transcribed the data in the form of recordings into a written form and analyzed them descriptively using ethnographic methods of communication through speech component analysis, and discourse analysis with the concept of pragmatics. The research result shows that the telling of the story of ulama/kiai in the speech can be used as a strategy for delivering messages among the members of Nahdlatul Ulama of Madurese ethnic group. It can raise the audience’s concentration to listen and understand the speech delivered by the speakers.